An energy efficient production of high moisture barrier nanocellulose/carboxymethyl cellulose films via spray-deposition technique. (15th December 2020) - Nadeem, Humayun; Naseri, Mahdi; Shanmugam, Kirubanandan; Dehghani, Mostafa; Browne, Christine; Miri, Simin; Garnier, Gil; Batchelor, Warren
Highlights: Spray deposited CMC/NC films are produced with significantly reduced drying time. CMC/NC films have moisture barrier properties comparable with plastic packaging. The environmental impact of CMC/NC films was lower than conventional packaging. Abstract: Nanocellulose (NC) films are considered as a prospective alternative to non-sustainable packaging materials, however, their higher embodied energy and limited moisture barrier properties are regarded as a huge constraint regarding their commercialization. This study aims to produce films with relatively low environmental impact and improved barrier performance. For this purpose, carboxymethyl cellulose (CMC) and NC were combined, and this resulted in multidimensional advantages. The mass production of films could be achieved in only 2 h (requiring at least 24 h under ambient conditions) when dried in an oven at 75 °C with enhanced mechanical properties and without compromising their dimensional stability. The moisture barrier properties of the NC/CMC films were improved up to 92 % compared with the NC films alone and the results achieved are comparable with packaging materials such as polyethylene terephthalate (PET), polycarbonates (PC) etc. Finally, the NC/CMC (1:1) films have low environmental impact compared with PET films.